Induced Membrane Bone Grafting Technique for Treatment of Large Postinfectious Acetabular Bone Defects - Zeng, Gerald Joseph (Arthroplast Today, 2020)
Management of large acetabular bone defects is challenging. The Masquelet technique has successfully reconstructed segmental defects in long bones arising from trauma, tumors, or infection but not been described for large acetabular defects. We present 3 cases of large acetabular bone defects arising from chronic prosthetic joint infection, treated via a novel induced membrane bone grafting technique, drawn from the Masquelet technique. All cases showed satisfactory clinical and radiological outcomes at midterm follow-up. This technique holds promise and can be an alternative means when treating large acetabular bone defects.